Using the Critical Path Method to Find Time of Constriction for Helicopters Airport Project in the Oil Fields - Abbas Johi Salah, Karrar; Saad Khalaf , Wakas (Journal of Economics and Administrative Sciences, 2023)
This research is considered one of the important researches in Maysan Governorate, as it focuses on the construction of helicopter airport project in the oil fields of the Maysan Oil Company, where the oil general companies in Maysan Governorate suffer from the cost of transporting the foreign engineering experts and the governing equipment of sustaining oil industry from Iraq's international airports to oil fields and vice versa. Private international transport companies transport foreign engineering from the oil fields to Iraqi airports and vice versa, and other international security companies take action to provide protection for foreign engineering experts during transportation. Hence, this process is very costly.     The objective of this research is to construct helicopters airport in the oil fields of the Maysan Oil Company, which can be reduced the required time for the arrival of foreign engineering experts and required equipment to the oil fields of the company by using the Critical Path Method (CPM). This may assist finding the time and cost of completing the project and drawing charts the project in light of the existence of non-traditional relationships between some activities in the project network, depending on the computer engineering software such as Primavera V6. 478 days were required to complete the project. Finally, a number of conclusions and recommendations are drawn up, and a number of future studies are suggested.Paper type: Research Paper